Leonardo to the internet : technology and culture from the Renaissance to the present - Misa, Thomas J. (Recorded Books, 2022)
Now updated--A comprehensive, 500-year history of technology in society. Historian Thomas J. Misa's sweeping history of the relationship between technology and society over the past 500 years reveals how technological innovations have shaped--and have been shaped by--the cultures in which they arose. Spanning the preindustrial past, the age of scientific, political, and industrial revolutions, as well as the more recent eras of imperialism, modernism, and global security, this compelling work evaluates what Misa calls "the question of technology." In this edition, Misa brings his acclaimed text up to date by drawing on current scholarship while retaining sharply drawn portraits of individual people, artifacts, and systems. Each chapter has been honed to relate to contemporary concerns. Globalization, Misa argues, looks differently considering today's virulent nationalism, cultural chauvinism, and trade wars. A new chapter focuses on the digital age from 1990 to 2016. The book also examines how today's unsustainable energy systems, insecure information networks, and vulnerable global shipping have helped foster geopolitical risks and instability and takes a look at the coronavirus pandemic from the perspective of Wuhan, China's high tech district. A masterful analysis of how technology and culture have influenced each other over five centuries, Leonardo to the Internet frames a history that illuminates modern-day problems and prospects faced by our technology-dependent world